Rhinopharyngitis and ENT morbidity among cement workers with long-term occupational exposure in Kongo Central Province, DRC - Kula , Marie Ditu; Pholo Manzimbala , Jean Paul; Etongola , Papy Steve Mbelambela; Gabriel, Lema; Mpenda, Gibency Mfulani; Mampuya, Eddy Mbambu; Nzanza, Christian Matanda; Okitambolo, Marie Catherine Mbutshu; Makani, Allen Kondi; Nzanza, Richard Matanda; Gedikondele, Jerome Sokolo (Orapuh Journal, 2025)
Introduction Cement mineral dust contains a variety of carcinogenic and non-carcinogenic substances that contribute to serious health effects. Purpose This study aimed to determine the ENT symptoms and diagnoses among workers exposed to cement dust. Methods A cross-sectional study was conducted between July and August 2024 among 270 workers in the exposed group (production, maintenance, transport, and handling workers) and 32 workers in the less exposed group (administrative staff and laboratory technicians) from the Kongo Cement Plant (CIMKO) in the DRC. A pre-designed questionnaire on ENT pathologies was administered to participants. Otoscopy, anterior rhinoscopy, and audiometry were performed. NO₂ (µg/m³) and SO₂ (µg/m³) concentrations were measured. Multivariate analysis was performed to determine the association between occupational exposure to cement dust and ENT symptoms and diagnoses. Results The annual average concentration of SO₂ was higher in the exposed group (15.54 µg/m³) and exceeded the threshold limit value (TLV) of the occupational exposure limit (OEL) adopted by NIOSH (2 ppm; 5 µg/m³). The exposed group had more than a sevenfold increased risk of pharyngitis, adjusted odds ratio (aOR) 7.4 (3.3–16.8), and more than a twofold increased risk of rhinitis, aOR 2.4 (1.4–4.1). Rhinosinusitis more than doubled the risk of presenting with pharyngitis and rhinitis, aOR 2.5 (1.6–3.9) and aOR 2.7 (1.2–6.5), respectively. Similarly, a duration of employment of ≥ 2 years increased the risk of pharyngitis more than fivefold, aOR 5.3 (3.6–15.2), and rhinitis more than threefold, aOR 3.6 (2.1–5.8). Conclusions Occupational exposure to cement dust was associated with ENT diagnoses, particularly a higher risk (5–21) of pharyngitis and rhinitis in the exposed group. This risk increased with longer duration of employment and a history of rhinosinusitis. Additionally, the mean concentration of SO₂ pollutants was higher in exposed workplaces compared with administrative areas.